2020
DOI: 10.1186/s12879-020-4796-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for gram-negative monomicrobial necrotizing fasciitis in southern Taiwan

Abstract: Background: Necrotizing fasciitis (NF) is a rare and life-threatening necrotizing skin and soft-tissue infection. Infectious pathogens of NF must be detected early and treated rapidly to prevent loss of limb or a fatal outcome. This study aimed to detect more reliable predictors between gram-negative and gram-positive monomicrobial NF of limbs. Methods: A total of 100 patients with limb monomicrobial NF were diagnosed prospectively from April 2015 to July 2018. These monomicrobial NF pathogens can be divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 37 publications
4
26
0
3
Order By: Relevance
“…We have set up the team "Vibrio necrotizing soft tissue infection (NSSTI) Treatment and Research (VTR) Group", which consists of professional staff working in various departments, including emergency medicine, orthopedic surgery, infectious diseases, intensive care unit (ICU), plastic surgery, and hyperbaric oxygen treatment center. Our team has successfully decreased the mortality rate of Vibrio NF from 38-13% (4,(10)(11)(12)(13)(14)(16)(17)(18)(19). However, we observed that the patients with monmicrobial necrotizing fasciitis caused by Aeromonas hydrophila and Aeromonas sobria still had the highest mortality rates up to 50% even we performed early diagnosis and immediately surgical interventions (4,12,14,16).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…We have set up the team "Vibrio necrotizing soft tissue infection (NSSTI) Treatment and Research (VTR) Group", which consists of professional staff working in various departments, including emergency medicine, orthopedic surgery, infectious diseases, intensive care unit (ICU), plastic surgery, and hyperbaric oxygen treatment center. Our team has successfully decreased the mortality rate of Vibrio NF from 38-13% (4,(10)(11)(12)(13)(14)(16)(17)(18)(19). However, we observed that the patients with monmicrobial necrotizing fasciitis caused by Aeromonas hydrophila and Aeromonas sobria still had the highest mortality rates up to 50% even we performed early diagnosis and immediately surgical interventions (4,12,14,16).…”
Section: Introductionmentioning
confidence: 84%
“…Monomicrobial gram-negative necrotizing fasciitis had been reported to have more fulminant clinical cources and higher motality than gram-positive necrotizing fasciitis in the past decade (4)(5)(6)(7)(8)(9)(10)(11). Vibrio vulnificus, Aeromonas hydrophila, and Klebsiella pneumoniae were the most frequently reported gram-negative aerobic pathogens of necrotizing fasciitis in southwest Taiwan (4, 8, 10-21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monomicrobial infection was diagnosed by isolating single pathogenic bacteria, and polymicrobial infections were diagnosed by isolating more than one pathogenic bacterium from soft tissue lesions and/or blood collected immediately after the patient’s arrival at the ED or during surgery [ 13 , 24 , 31 ].…”
Section: Methodsmentioning
confidence: 99%